Psycholinguistic Extracts and Socio-Cultural Imprints in Job Application Discourses: A Genre Analysis - Emmanuel J. Songcuan (Philippine Association of Institutions for Research, Inc., 2012)
Genres represent purposive and staged ways of communicating in a culture and enacting a range of important institutional practices. Genre studies have paved the way for understanding the way discourse is used in academic, professional, and institutional contexts. This paper analyzed the psycholinguistic realization and drew out socio-cultural imprints in the construction of application letter and resume in the Philippine setting. Qualitative and quantitative methods were employed in the analysis of job application documents representing different professions to determine the generic structure and the linguistic features of the moves and strategies that accomplish the communicative functions of the genres. Employers' group survey and job interview extracts were also used to cross-validate and provide snapshots on the interpretations made. A seven-move and a five-move generic structure occurring in a flexible sequence define the composition of job application letter and resume, respectively. The construction of these two types of discourse is influenced and constrained by the applicant's psycholinguistic repertoire, professional background, and socio-cultural milieu. A genre-based pedagogy is recommended to sensitize Filipinos of the existing genres and textlinguistic variations in the workplace.